APLIKASI METODE GEOLISTRIK TAHANAN JENIS UNTUK MENENTUKAN ZONA INTRUSI AIR LAUT DI KECAMATAN GENUK SEMARANG - Nisa, Khoirun; Yulianto, Tony; Widada, Sugeng (BERKALA FISIKA, 2012)
An interpretation has been conducted to the salt water spreading in the district of SemarangÂ city Genuk area by the geoelectrical method of resistivity using Schlumberger electrode configuration.Acquisition of field data were processed using Ip2win program whose results are used toÂ describe the resistivity cross-section area of research. Resistivity cross-section was combined with thedistribution of groundwater sanility from electrical conductivity value approach to determine thezoning of sea water intrusion in the study area.Zone of sea water intrusion in the district of Semarang city Genuk are consist regionKarangroto and Sembungharjo starting from a depth of 80 meters, Bangetayu west starting from adepth of 100 meters, 140 meters depth Genuksari start, and Trimulyo ranging from a depth of 200meters with values of electrical conductivity 16.550 Î©m.Key Words : Geo-electrical, sea water intrusion